New independent media in the digital media. The online radio station in Spain: Case study of ‘Carne Cruda’ and ‘Radiocable’ - Silvia Olmedo Salar; Paloma López Villafranca (Index Comunicación, 2018)
The possibilities offered by Internet to both users and media have enabled radio to be the ideal space to work with economic and political freedom, facing the media monopoly. The use of smartphones, the emergence of digital sound platforms and streaming provide a wide range of sound contents (Pedrero, 2015). Free radios “give coherence to movements that claim them as a vector of change and social participation” (Chaparro, 2008). The type of radio stations we analyze in this research arise without being considered community radios, although they have a close relationship with this type of stations, whose essence is serving the interests of citizens. To achieve economic and political independence, online stations have used the formula of crowdfunding provided by their own listeners. In the current investigation we analyze the case of two online radios supported through crowdfunding which establish a relationship with the public based on public service: Carne Cruda and Radiocable. To carry out the study, a qualitative and quantitative methodology has been applied to offer an integral analysis of the phenomenon studied.